Street language in Dùndún Drum Language - Oludare, Olupemi (International Library of African Music, 2022)
Dùndún drum language is a practice of speech surrogacy employed by dùndún drummers in Yoruba culture. The dùndún drummers play sequences of melo-rhythmic patterns; a form of communication that employs musical and linguistic elements, comprehensible to listeners knowledgeable in the Yoruba language. Although these sequenced patterns are sourced from Yoruba everyday sentences and oral genres (proverbs, poetry, praise-chants, and idiomatic phrases), the drummers also embrace other social narratives. These include the popular linguistic expressions in public spaces referred to as “street language.” This is because the streets serve as spaces for social life, musical and cultural imaginaries, musical and language expressions, and identity. This street language, referred to as “ohùn ìgboro” in Yoruba, include slang (saje), slurs (òtè), neologies (ènà), satire (èfè), dance-drum patterns (àlùjó), and socio-political slogans (àtúnlò-èdè). This article explores the influence of street language on dùndún music. This article follows an ethnographic model, with an analysis of the content of the dùndún music and its associated texts. The article’s findings include the extent to which the two cultures have overlapped, and the various socio-cultural benefits of adopting the language of each other’s cultural practices. In the process, the article contributes to the debate on authenticity and social structure in Yoruba culture. The article emphasises the need for an integrated research approach of music and language and their interrelationship to street cultures in Nigeria.
Keywords: Drum language; Culture; Musical instruments; Yoruba (African people); Drum music; Drum; Yoruba Art; Street Language; Street Culture; Dùndún (Instrument); Melo-rhythm; Ethnography; Nigeria; African Music; Drum (Instrument)